Indonesian Post Graduate Student’s Motivation as an Autonomous Learner in Overseas University - Dzikrina Mardhotila; Syafi’ul Anam; Slamet Setiawan (Linguistic, English Education and Art (LEEA) Journal, 2020)
This study investigates the motivation of Indonesian postgraduate student as an autonomous learner in overseas university. This study focuses on answering a research question; (1) how the learner motivates himself for being autonomous learner. The qualitative method was used to fulfill the objective of the study. The data was collected from interview section with the student. It was transcribed and analyzed descriptively. The result shows that the student is an autonomous learner who has intrinsic and extrinsic motivation in learning language in overseas university. It can conclude that this study will enrich the discussion which relates to students’ motivation for being an autonomous learner especially in overseas university. Keywords: Autonomous Learner, Motivation, Intrinsic and Extrinsic